Identifying Human Factor Causes of Remotely Piloted Aircraft System Safety Occurrences in Australia - John Murray; Steven Richardson; Keith Joiner; Graham Wild (Aerospace)
Remotely piloted aircraft are a fast-emerging sector of the aviation industry. Although technical failures have been the largest cause of accident occurrences for Remotely Piloted Aircraft Systems (RPASs), if they are to follow the path of conventionally crewed aviation, Human Factors (HFs) will increasingly contribute to accidents as the technology of RPASs improves. Examining an RPAS accident database from 2008–2019 for HF-caused accidents and coding to the Human Factors Analysis and Classification System (HFACS) taxonomy, an exploration of RPAS HFs is carried out and the predominant HF issues for RPAS pilots identified. The majority of HF accidents were coded to the Unsafe Acts level of the HFCAS. Skill errors, depth perception and environmental issues were the largest contributors to HF RPAS safety occurrences. A comparison with other sectors of aviation is also made where perception issues were found to be a greater contributor to occurrences for RPAS pilots than for other sectors of aviation. Developing appropriate training programs to develop skilled RPAS operators with good depth perception can contribute to a reduction in RPAS accident rates. The importance of reporting RPAS incidents is also discussed.